5- Les Sciences Sociales en Afrique de l’Ouest Francophone - Diouf, Makhtar (Africa Development, 2023)
From this paper on the role of Social Science in Africa, more parti cularly in Francophone Africa the following conclusions may de drawn : 1 ) On the whole a majority of students (2/3) tend to opt for Social Science. 2) Nevertheless, generally speaking, African governement gives priority to the study of Social Science within the range of available University disciplines. There are of course both objective and material reasons for that : The funds available for University studies being rather limited, there is a tendency to channel them towards the most optimal utilization possible with a view to short term returns i.e the technical disciplines and the natural sciences. The usefulnes of Social Science in the development strategy is still not fully understood in Africa. The various centres for Social Science training only exist for the purpose of supplying the necessary adminis trative cadres to replace the outgoing technical assistants. Furthermore there is a political reason in that a number of African governments consider Social Science as a breeding ground for reflections on past policies, hence as a factor of dissent and agitation. A number of African universities were founded in the early seventies only a short time after the student revolt which is universally recognized as the mecca of Social Science. This fact only strenghthens the political distrust vis-à-vis Social Science in African universities which in any case remain under French control. 3) However the importance given to Social Science is far from being the same in every country in Africa. In countries like Senegal, the Ivory Coast and Zaire where there are well-established universities, Social Science plays a relatively important role both at the educational and research level which however is not the case for a country like Cameroun where the university was founded in the early sixties and has acquired a certain degree of prestige. On the other hand the recently established and small university of Benin has been remarkably active in the field of Social Science. In Upper Vol. a, Mali, and Togo Social Science occupies the place of a poor relative, and their governments have clearly opted for an expansion in the technical disciplines